The Existence of Quick Response Code Indonesian Standard (QRIS) as a National Product in International Economic Competition - Ahmad Rizal Roby Ananta; Muhammad Asrul Maulana; Savira Risti; Vara Yuniar Abela; Cici Fanisa Yulia Dwi Jayanti (JURNAL PUSPAKA, 2025)
This study aims to analyze the strategic contribution of the Quick Response Code Indonesian Standard (QRIS) in supporting Indonesia's economic sovereignty amid the dominance of foreign payment systems. This study uses a qualitative method with a case study approach to the dynamics of international pressure on the sustainability of QRIS, especially from the United States. Data is obtained through a review of actual news and official documents from Bank Indonesia. The findings show that QRIS not only encourages transaction efficiency and expansion of financial access, but also strengthens the independence of the national financial system. Cross-country cooperation shows the potential of QRIS as a regional economic hub. The conclusion of this study confirms that QRIS is a significant domestic innovation in building competitiveness and economic sovereignty in the digital era.